Perancangan Ulang Visual Branding CE Homewear untuk Memperkuat Citra Merek di Pasar Homewear - Bestin, Bakti; Soemarta, Gifari Aji; Kusuma, Andi Ryan (Universitas Informatika dan Bisnis Indonesia, 2024)
PT Mitra Emeraldye Cotama is a company that carries out production activities in the fashion sector with the trademark CÉ Homewear. CÉ Homewear implements business-to-business (B2B) transactions. However, many people do not understand the business purpose of CÉ Homewear, assuming that the company only sells clothes, not as a producer with B2B transactions. From this basis, a research was conducted that aims to increase consumer brand awareness of the company in the redesign of CE Homewear's visual branding. In this design process using the Design Thinking method. Data collection by conducting interviews in order to obtain clear truthful information, followed by questionnaires to obtain data from the consumer's point of view and literature studies to become a reference for making designs. The data that has been collected will be analyzed using the SWOT method. Followed by a communication design strategy using the AISAS method. The result of CE Homewear's visual branding redesign is an increase in consumer brand awareness as evidenced by the increase in social media engagement and the increase in CE Homewear's new partners. The increase in engagement increased the engagement rate on the first reels post by 0.35% and 0.69% for the second reels post. In addition, the increase in the number of new partners by 16 people is an indicator of the success of a company's brand awareness.